IMPROVED RATIO OF GERAM RESTRICTIONS AND REDUCTION OF PAHAT PAID WITH MODIFIED WEARS OF PAVING CUTS AT DVA MACHINE - Didik Nurhadiyanto; Mujiyono Mujiyono (Jurnal Penelitian Saintek, 2005)
This  research   is   aimed   to   determine   the   differences   of   chipcompression ratio and tool wear between a modified double cuttingtool and a standard cutting tool.The workpiece is made of VCN 150 with a dimension of e 1,75 inchand 200 mm long. Because the diameter of the blank is constant, the spindle rotation is set to 265 RPM  Both cutters use the same coolant and have the same  cutting angle.  The properties  to be varied are depth  of  cuts  and feed   Depth  of  cuts  of standard  cutting  tool  is formulated by the blank diameter substituted by the final diameter and than divided by two. The same formulation  goes for  depth of cuts of modified cutting tool. Tool wears and chip compression ratio values chosen  is  the  biggest  value  on  each  cutting  edge.  Steps  of  this research one: Record the tool wear and chip compression ratio for each feed,  which one 0,043; 0,066; 0,0875; and 0,/75  mmlrev while using depth of cuts of 0,5; I; 1,5 and 2 mm. Each treatment is done 5 times or each cutting stroke  and the average  is  taken  as a result. Comparing tool wear and chip compression ratio resulted from  the utilization of modified cutting tool and standard tool.It can be concluded from  the result  of this research  that (I)  using modified cutting tool, there is an improvement of chip compression ratio  equal  to  6,74%   compared  to  the  standard  cutter  (2)  using modified cutting tool there is a reduction tool wear equals to 14,53% compared the standard cutting /001.